2022
DOI: 10.3389/fphar.2022.850586
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Related Lymphedema: Mysteries, Mechanisms, and Potential Therapies

Abstract: The lymphatic circulation is an important component of the circulatory system in humans, playing a critical role in the transport of lymph fluid containing proteins, white blood cells, and lipids from the interstitial space to the central venous circulation. The efficient transport of lymph fluid critically relies on the rhythmic contractions of collecting lymph vessels, which function to “pump” fluid in the distal to proximal direction through the lymphatic circulation with backflow prevented by the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 140 publications
(229 reference statements)
1
8
0
1
Order By: Relevance
“…The lymphatic circulation plays an important role in transporting lymph fluid, including leukocytes, proteins, and lipids, from the interstitial space to the central venous circulation 16 . Lymphatic vessels contract rhythmically, transporting lymph and inhibiting reflux by valves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphatic circulation plays an important role in transporting lymph fluid, including leukocytes, proteins, and lipids, from the interstitial space to the central venous circulation 16 . Lymphatic vessels contract rhythmically, transporting lymph and inhibiting reflux by valves.…”
Section: Discussionmentioning
confidence: 99%
“…When there is a problem with the lymphatic circulation, fluid accumulates in the interstitial space 17 . Recently, the incidence of lymphedema is increasing due to surgery and radiotherapy related to malignant neoplasms 11 , 16 . Most of the standard treatment for lymphedema is physiotherapy such as lymphatic drainage and compression bandage.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium channel blockers (CCBs) are a commonly used pharmaceutical to treat cardiac arrhythmias and vascular disease including hypertension and angina. 5 Peripheral edema is a potential side effect of CCBs and ranges from 5% to 70% based on the drug, 21,22 time of intake, 23 patient age, 24 and duration of therapy. 21 CCBs cause vasodilation of the arterioles in the absence of venous dilation, resulting in increased capillary pressure.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…25 In addition, it is postulated that CCBs inhibit the contractions of the lymphatic system, which could result in the reduction of lymphatic flow and subsequent development of lymphedema. 5 Hypertension and/or its treatment are risk factors associated with lymphedema. 26 In a nested casecontrol study, Stolarz et al 6 found that CCBs were significantly associated with an increased risk of lymphedema in patients with breast cancer.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
See 1 more Smart Citation